All Days 2007
DOI: 10.2118/108344-ms
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Coordinated Control of Pump Rates and Choke Valve for Compensating Pressure Fluctuations during Surge and Swab Operations

Abstract: In this paper we present new methods for coordinated control of pump rates and choke valve for compensating pressure fluctuations during surge and swab operations. In hydrocarbon well drilling, automatic control of the choke valve improves the control of the bottom-hole pressure. This has made it possible to drill wells where it previously was not possible to reach total depth, due to narrow pressure margins in the reservoir. This concept is developed further in this paper, to also include au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…Automatic control of the bottom hole pressure in a drilling operation has been studied by [1,6,7]. However, in these works, the backpressure pump is assumed to be absent in the drilling rig.…”
Section: Figure 1 Simplified Diagram Of An Oil Well Drilling Systemmentioning
confidence: 99%
“…Automatic control of the bottom hole pressure in a drilling operation has been studied by [1,6,7]. However, in these works, the backpressure pump is assumed to be absent in the drilling rig.…”
Section: Figure 1 Simplified Diagram Of An Oil Well Drilling Systemmentioning
confidence: 99%
“…Rasmussen and Sangesland (2007) compared and evaluated different MPD methods for compensation of surge and swab pressure. In Nygaard et al (2007a), it is shown that surge and swab pressure fluctuation in the bottom hole pressure during pipe connection can be suppressed by controlling the choke and main pump. Nygaard et al (2007b) used a nonlinear model predictive control algorithm to obtain optimal choke pressure for controlling the bottom-hole pressure during pipe connection in a gas dominant well.…”
Section:  Increasing the Rate Of Penetration (Rop)mentioning
confidence: 99%
“…In many cases the bottomhole pressure (the pressure at the bit) is used as the variable to control [4], [5], [6], [7]. The bottomhole pressure is measured, but the signal is usually transmitted by mud-pulse telemetry which is powered by a mud flow turbine.…”
Section: A Pressure Controlmentioning
confidence: 99%
“…Previous attempts at using low order models for control and estimation of the bottomhole pressure can be found in [14] and [5]. In [14] nonlinear model predictive control (NMPC) was used together with an unscented Kalman filter to control the bottomhole pressure.…”
Section: B Pressure Estinlationmentioning
confidence: 99%
See 1 more Smart Citation